Relación entre las tasas de crecimiento de urbanización, consumo de energía eléctrica, capital humano y emisiones de CO2, a través de un análisis de cointegración para datos de panel a nivel mundial, período 1986-2016 - Ramos Arias, Ramiro Alejandro (2019)
There is empirical evidence that the increase in urbanization, energy production and consumption has a positive effect on environmental pollution, which is concentrated mostly in countries with a high industrial sector. In this context, the objective of this research is to examine the relationship between CO2 emissions, the growth rate of urbanization, electricity consumption and human capital in 114 countries worldwide classified according to their level of per capita income using the World Bank's ATLAS method (2017) during the period 1986-2016 through a co-integration and causality analysis in order to propose policies to reduce CO2 emissions and thus mitigate the adverse effects of climate change. The results obtained suggest that the growth rates of CO2 emissions, urbanization, electricity consumption and human capital have a balance relationship in the short and long term. The results of the causality test indicate that there is bi-directional causality between CO2 emissions and Urbanization, between CO2 emissions and Electricity Consumption, and between CO2 Emissions and Human Capital for all income groups except low-income countries. Policies aimed at improving the industrial structure are suggested, along with greater efficiency in electricity production, as well as increasing the share of renewable energy to reduce CO2 emissions.